Exercise-Induced Improvements to Whole Body Glucose Metabolism in Type 2 Diabetes: The Essential Role of the Liver - Warner, Shana O.; Yao, Michael V.; Cason, Rebecca L.; Winnick, Jason J. (Frontiers in Endocrinology, 2020)
Type 2 diabetes (T2D) is a metabolic disease characterized by obesity, insulin resistance and the dysfunction of several key glucoregulatory organs. Among these organs, impaired liver function is recognized as one of the earliest contributors to impaired whole-body glucose homeostasis, with well characterized hepatic insulin resistance resulting in elevated rates of hepatic glucose production (HGP) and fasting hyperglycemia. One portion of this review will provide an overview of how HGP is regulated during the fasted state in healthy humans and how this process becomes dysregulated in patients with T2D. Less well appreciated is the liver’s role in postprandial glucose metabolism, where it takes up and metabolizes one-third of orally ingested glucose. An abundance of literature has shown that the process of hepatic glucose uptake is impaired in patients with T2D, thereby contributing to glucose intolerance. A second portion of this review will outline how hepatic glucose uptake is regulated during the postprandial state, and how it becomes dysfunctional in patients with T2D. On a positive note, it is well known that exercise training has an insulin-sensitizing effect on the liver, which contributes to improved whole-body glucose metabolism in T2D patients, thereby making it a cornerstone in the management of the disease. To this end, we thoroughly discuss the impact of exercise on hepatic glucose metabolism, referencing key findings in the literature. At the same time, we discuss sources of heterogeneity that contribute to inconsistent findings in the field and point out important topics for future investigation.